Chremylus encounters Blepsidemus: The first quiproquo? (Aristophanes’ Wealth 332–414) - Fernandez, Claudia Nelida (2021)
Blepsidemus is associated with the comic figure of the bomolochos, as he serves as a ludicrous counterpoint for Chremylus in his debate with Poverty. But the moment in which Blepsidemus demonstrates all of his potential as a dramatic character occurs during the previous scene to the agon (vv. 332–414), when he takes part in a dialogue with his friend. This was highlighted as the only example of quiproquo (“misunderstanding”) in Aristophanes’ plays. The aim of this paper is to explore the aesthetic efficacy of its composition and its semantic impact on the comedy.